Lipolytic response of adipose tissue and metabolic adaptations to long periods of fasting in red tilapia (Oreochromis sp., Teleostei: Cichlidae) - Dias Junior, Walter; Baviera, Amanda M. [UNESP]; Zanon, Neusa M.; Galban, Victor D.; Garófalo, Maria Antonieta R.; Machado, Celio R.; Bailão, Elisa F. L. C.; Kettelhut, Isis C. (FapUNIFESP (SciELO), 2016)
Adaptive changes of carbohydrate and lipid metabolism induced by 7, 15, 30, 60, 90, 150 and 200 days of fasting were investigated in red tilapia (Oreochromis sp.). Plasma glucose, lactate and free fatty acids (FFA) levels, liver and muscle glycogen and total lipid contents and rates of FFA release from mesenteric adipose tissue (MAT) were measured. Plasma glucose levels showed significant differences only after 90 days of fasting, when glycemia was 34% lower (50±5mg.dL-1) than fed fish values (74±1mg.dL-1), remaining relatively constant until 200 days of fasting. The content of liver glycogen (»15%) in fed tilapia fell 40% in 7 days of food deprivation. In 60, 90 and 150 days of fasting, plasma FFA levels increased 49%, 64% and 90%, respectively, compared to fed fish values. In agreement with the increase in plasma FFA, fasting induced a clear increase in lipolytic activity of MAT incubated in vitro. Addition of isobutylmethylxanthine (cAMP-phosphodiesterase inhibitor) and isoproterenol (non selective beta adrenergic agonist) to the incubation medium induced a reduction of lipolysis in fasted fish, differently to what was observed in mammal adipose tissue. This study allowed a physiological assessment of red tilapia response to starvation.
Keywords: Adipose tissue; Adrenoreceptor; Lipolysis; Liver glycogen